Infrastructuring coastal futures: Key trajectories in Southeast Asian megacities - Herbeck, Johannes; Flitner, Michael (DIE ERDE – Journal of the Geographical Society of Berlin, 2019)
The search for suitable adaptation pathways to accommodate for rising sea levels resulting from global climate change is an ongoing concern for many megacities in Southeast Asia and beyond. Addressing already existing challenges resulting from land subsidence and increased occurrence of inland flooding, adaptation can take varied forms and cover widely differing concerns, spaces and time spans. Based on research carried out in the cities of Singapore, Jakarta (Indonesia), and Manila (Philippines), this paper looks at some key trajectories of current adaptation planning. We argue that the processes of infrastructuring coastal futures in these cities are characterized by different aims and measures that overlap and converge in their material effects but also compete in articulating diverging new claims to the coast. In this perspective, we describe and analyze three main trends of infrastructuring coastal futures: the securitization of coastal futures by way of transforming disaster risk reduction practices and integrating new policy concerns, the greening of coastal spaces in material and operational terms, and finally, the valorization of coastal areas through reclamation, waterfront development and the creation of high-end real estate. Along these three trajectories, coastal adaptation planning becomes a key force that can influence virtually every sector of urban development and governance, and has strong implications for the futures of coastal cities in social and political terms.